BRAT1 links Integrator and defective RNA processing with neurodegeneration - Cihlarova, Zuzana; Kubovciak, Jan; Sobol, Margarita; Krejcikova, Katerina; Sachova, Jana; Kolar, Michal; Stanek, David; Barinka, Cyril; Yoon, Grace; Caldecott, Keith W; Hanzlikova, Hana (Nature communications, 2022)
Mutations in BRAT1, encoding BRCA1-associated ATM activator 1, have been associated with neurodevelopmental and neurodegenerative disorders characterized by heterogeneous phenotypes with varying levels of clinical severity. However, the underlying molecular mechanisms of disease pathology remain poorly understood. Here, we show that BRAT1 tightly interacts with INTS9/INTS11 subunits of the Integrator complex that processes 3' ends of various noncoding RNAs and pre-mRNAs. We find that Integrator functions are disrupted by BRAT1 deletion. In particular, defects in BRAT1 impede proper 3' end processing of UsnRNAs and snoRNAs, replication-dependent histone pre-mRNA processing, and alter the expression of protein-coding genes. Importantly, impairments in Integrator function are also evident in patient-derived cells from BRAT1 related neurological disease. Collectively, our data suggest that defects in BRAT1 interfere with proper Integrator functions, leading to incorrect expression of RNAs and proteins, resulting in neurodegeneration.
Keywords: histony; Neurodegenerative Diseases; posttranskripční úpravy RNA; neurodegenerativní nemoci; Histones; fenotyp; Mutation; mutace; Phenotype; lidé; jaderné proteiny; Nuclear Proteins; Humans; RNA Processing, Post-Transcriptional